2022
DOI: 10.3390/su14063514
|View full text |Cite
|
Sign up to set email alerts
|

The 2020 Maize Production Failure in Ghana: A Case Study of Ejura-Sekyedumase Municipality

Abstract: This paper examines the causes of widespread maize production failure in Ghana during the 2020 minor growing season. A mixed-methods approach was used to study smallholder maize farmers in the Ejura-Sekyedumase Municipality to provide a holistic understanding of the factors behind the maize production failure and to inform policy interventions. The results show that the decline in maize grain yield was caused by the failure of the minor season rains and, more importantly, the destruction of maize plants by fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Their study suggests that current maize models may not adequately capture the impact of climate extremes, specifically heat and drought, on maize photosynthesis and yield. In their survey, Obour et al [37] studied the primary causes of maize production failure in Ghana. They revealed that factors such as poor soil quality, inadequate farm inputs and under-resourced mechanisation had a lesser impact on maize production failure than drought conditions that are unfavourable for maize growth.…”
Section: Discussionmentioning
confidence: 99%
“…Their study suggests that current maize models may not adequately capture the impact of climate extremes, specifically heat and drought, on maize photosynthesis and yield. In their survey, Obour et al [37] studied the primary causes of maize production failure in Ghana. They revealed that factors such as poor soil quality, inadequate farm inputs and under-resourced mechanisation had a lesser impact on maize production failure than drought conditions that are unfavourable for maize growth.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, maize is one of the most important cereals in the world and a staple food in many households. It is also a source of animal feed and a fundamental product in the food industry [2,3]. World production is estimated at 1192 Mt, with the largest producers being the United States, China, Brazil and Mexico [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, corn is one of the most important cereals in the world and a staple food in many households. It is also a source in animal feed and a fundamental product in the food industry [2,3]. World production is estimated at 1,192 Mt, with the largest producers being the United States, China, Brazil and Mexico [4].…”
Section: Introductionmentioning
confidence: 99%